Phytochemical profiling and cardioprotective activity of Vernonia amygdalina ethanol extract (VAEE) against ISO-induced cardiotoxicity in rats - Arya Tjipta Prananda; Aminah Dalimunthe; Urip Harahap; Rony Abdi Syahputra; Sony Eka Nugraha; Putri Cahaya Situmorang; Yee Teck Fah; Adrian; Jekson Martiar Siahaan; Adrian Joshua Velaro; Besa Bilakaya; Muhammad Andika Yudha Harahap (Pensoft Publishers, 2023)
Cardiovascular disorder is the leading cause death in the world, one of them are acute myocardial infarction (AMI) which associated with hypertension and cardiac remodeling. ISO may cause inflammation, enhance the production of oxidative stress while decrease the antioxidant defensive system, myocardium impairment, calcium overload, enhanced cyclic adenosine monophosphate level, intracellular acidosis, and altered membrane permeability. Vernonia amygdalina (VA) is a medicinal plant with antioxidant and anti-inflammatory properties. This study investigated the potential cardioprotective effect of VA on ISO-induced cardiac toxicity in rats. Male Wistar rats were randomly divided into six groups: ISO (ISO), quercetin 100 mg/kg plus ISO (ISO+QR), VA ethanol extract 100, 300, 500 mg/kg plus ISO (ISO+VA100, ISO+VA300 and ISO+VA500). ISO was administered subcutaneously (85 mg/kg) on days 15 while quercetin and VA extract and was given orally for 14 days. At the end of the experiment, the blood was taken from the heart were analyzed for markers of cardiac, oxidative stress and inflammation. The ISO group exhibited significant (p<0.05) elevation of cardiac biomarkers such as lactate dehydrogenase (LDH), creatine kinase-MB (CK-MB), troponin-T, and BNP as well as increased oxidative stress markers such as malondialdehyde (MDA) and reduced antioxidant enzyme superoxide dismutase (SOD), catalase (CAT), and Glutathione peroxidases (GPx). Additionally, the ISO group had elevated levels of pro-inflammatory cytokines interleukin-1 (IL-1), interleukin-6 (IL-6), Highly sensitive c reactive protein (HsCRP) and tumor necrosis factor-alpha (TNF-α). Treatment with VA extract significantly (p<0.001) reduced these parameters in the VA+ISO group compared to the ISO group. These findings suggest that VA has a potential protective effect against ISO-induced cardiotoxicity by reducing oxidative stress, apoptosis, and inflammation. (The graphiccal abstract can be seen in the Fig. 1).